Always a catch!: how I punched my way into marrying a prince, 3 - Momoyo, Mayo; Mito, Itsuki (Always a catch!, 2025)
Newly engaged Maria is ready to return to Rubini and reunite with Prince Renato, having mended things with her father in Muro. But her journey takes a detour when she hears of a missing girl and troubled villagers. Ever the spirited heroine, Maria can't ignore a cry for help-Prince Renato will have to wait while she sets off on a rescue mission.